PENGGUNAAN MEDIA SOSIAL (YOUTUBE) SEBAGAI MEDIA INOVATIF DALAM PEMBELAJARAN DI MADRASAH GRESIK - Abdulloh, Abdulloh; Fahmi, Mochamad Zakki; Siswanto, Imam (Universitas Negeri Surabaya, 2019)
The community service activities have been carried out at Madrasah Aliyah Masyhudiyah Gresik. Thepurpose of service is: 1) providing understanding to teachers in making learning material throughYouTube, 2) providing motivation to teachers, 3) building teachers' confidence, and 4) using YouTube forfun learning tools. Methods of activities are lectures, demonstrations, workshops and training using theCamtasia application. Data collection techniques are based on the results of the pretest - posttest andparticipatory approach. Data analysis to measure the success category is done by calculating thepercentage of correct answers for each aspect asked, the percentage of learning videos made and thenumber of learning videos uploaded. The results of the activities are: 1) the teacher's understanding inmaking construction of video-based learning materials on average increased by 52%, 2) 100% of teachershave made videos for learning media using the Camtasia application, 3) 30% of teachers have uploadedlearning videos on social media YouTube This activity resulted in an increase in teacher understandingrelated to the importance of using YouTube as a learning medium and videos containing learning materialscreated by madrasa teachers.